Cultivation Methods Using Kajarula Technology to Increase the Productivity of Seaweed (Kappaphycus alvarezii) - Siska Ayu Wulandari (International Journal Labs, 2025)
Seaweed (Kappaphycus alvarezii) is a potential marine biological resource in Indonesia, especially in Palasa Village, Sumenep, East Java. The conventional (long-line) method applied in cultivation is still not effective and efficient enough. The urgency in this study is that the decrease in production output is influenced by environmental disturbances, such as pest attacks, strong currents and waves, as well as the problem of using plastic bottle floats in conventional cultivation methods that are not environmentally friendly. Therefore, there is a need to develop cultivation methods to increase seaweed productivity. This study aims to analyze seaweed productivity using Kajarula (Seaweed Net Bag) technology at the cultivation location of Palasa Village, Sumenep, East Java. This study uses the Group Random Design (RAK) method. The research began with the measurement of the physical-chemical quality of the waters, the creation of a design for making Kajarula from the clumps, monitoring the growth of seaweed, monitoring the quality of waters, monitoring pests and diseases, and the productivity of seaweed. Data analysis using seaweed productivity parameters including biomass production, relative growth, growth, absolute growth rate, and total harvest. The data obtained is then tabulated using the Ms. Excel application to produce representative data in the form of graphs and tables, and analyzed descriptively. From the results of the study, seaweed cultivated for 42 days produced an average biomass production of 5.54 ± 0.27 kg/unit, a relative growth of 153.41 ± 10.97%/day; growth 754 ± 27 g/binding point; absolute growth rate of 239.32 ± 21.95 g/day; and a total harvest of 5.26 – 5.82 kg/unit of bag. The water quality condition in these waters is in the optimal range in supporting the growth of seaweed. Productivity of cultivation, seaweed using Kajarula technology shows optimal growth and yield.